Emprunt et créativité langagière, le cas du fraçais dans la chanson algérienne (raï et rap). - BOUMEDINI Belkacem (My University, 2009)
The research we are undertaking is about languages present in the rai and rap songs in Algeria. Our work fits into urban sociolinguistic and pursues the reflection conducted in the multilingualism situations in general and the Algerian situation in particular. The objective of our reflection is to explain the why and the wherefore of the resort to French in the two Algerian musical styles (Rai and Rap). The starting idea of the present work was born out from the following report: in the rai and rap texts, there is a contact between the Algerian Arabic (mother tongue) and French, second language in the young people`s language practices. We have started from the hypothesis stating that this linguistic mixture is a logic consequence of the contact of the two countries situated on the two shores of the Mediterranean, and where the commercial, political and cultural exchanges have never been interrupted. For our theoretical foundation, we have thought it was a good idea to define the concepts in relation with our study in addition to a historical insight on the two musical phenomena in question. The practical part was based on a thematic and sociolinguistic analysis of the corpus, which allowed us to locate the alterations undergone by the French language in contact with the Algerian Arabic, and the cases where the terms have not been integrated; in addition to the other languages used by the singers, classical Arabic, English, and even Spanish.
Keywords: Rai, Rap, language creativity, language contact, bilingualism, multilingualism, borrowing, code switching.